Internet Browsing Habits and Domain Choice Preferences of Economic Agricultural Engineers - Dövényi-Nagy, Tamás (Acta Agraria Debreceniensis, 2004)
The findings below are based on a questionnaire survey carried out in order to establish an internet-based service at the Center of Agricultural Sciences of Debrecen University:• The typical target group of the service in the short run with a weekly average of 5.9 hours on the web is more active than that for average Hungarian, adult Internet users.• A professional webportal with a searchable database, primarily incorporating an archive of organized agricultural news, articles, publications, fits well into the internet habits of the target group, which mainly consists of keyword-based information searces and browsing of the latest news.• The group prefers a short, easily recognizable domain name that refers to agriculture. Accents and foreign sounding words are not taken into account during selection.• As result of the choice from 43 eligible domains, the order would be the following: agrarunio, agroland, farmvilag, infoagro, farmland.• The names of magyargazda.hu, agrotrend.hu, agromester.hu, agronomus.hu are acceptable from the individual ideas.